Nanoparticle binding attenuates the pathobiology of gastric cancer-associated Helicobacter pylori. Issue 3 (5th January 2018) - Westmeier, Dana; Posselt, Gernot; Hahlbrock, Angelina; Bartfeld, Sina; Vallet, Cecilia; Abfalter, Carmen; Docter, Dominic; Knauer, Shirley K.; Wessler, Silja; Stauber, Roland H.
Abstract : Binding of nanoparticles on the surface of H. pylori results in the attenuation of bacterial cancer-associated pathobiology. Abstract : Enteric bacteria may cause severe diseases, including gastric cancer-associated Helicobacter pylori . Their infection paths overlap with the oro-gastrointestinal uptake route for nanoparticles, increasingly occurring during environmental or consumer/medical exposure. By comprehensive independent analytical methods, such as live cell fluorescence, electron as well as atomic force microscopy and elemental analysis, we show that a wide array of nanoparticles (NPs) but not microparticles form complexes with H. pylori and enteric pathogens without the need for specific functionalization. The NP-assembly that occurred rapidly was not influenced by variations in physiological temperature, though affected by the NPs' physico-chemical characteristics. Improved binding was observed for small NPs with a negative surface charge, whereas binding could be reduced by surface 'stealth' modifications. Employing human gastric epithelial cells and 3D-organoid models of the stomach, we show that NP-coating did not inhibit H. pylori 's cellular attachment. However, even the assembly of non-bactericidal silica NPs attenuated H. pylori infection by reducing CagA phosphorylation, cytoskeletal rearrangement, and IL-8 secretion. Here we demonstrate that NP binding to enteric bacteria may impact their pathobiology which could be further exploited to rationally modulate the (patho)biology of microbes by nanomaterials.